1993
DOI: 10.1128/aac.37.6.1334
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double-blinded trial of rifampin with either novobiocin or trimethoprim-sulfamethoxazole against methicillin-resistant Staphylococcus aureus colonization: prevention of antimicrobial resistance and effect of host factors on outcome

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a major pathogen in hospitals. Current antimicrobial regimens for eradicating colonizing strains are not well defined and are often complicated by the emergence of resistance. The combination of novobiocin plus rifampin in vitro and in vivo was found to prevent the emergence of resistant populations of initially susceptible strains of MRSA, particularly resistance to rifampin.We therefore studied, in a randomized, double-blind, multicenter comparative trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
78
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(82 citation statements)
references
References 46 publications
4
78
0
Order By: Relevance
“…This is in agreement with one controlled trial that demonstrated the efficacy of trimethoprim/sulfamethoxazole plus rifampicin for MRSA decolonization. 27 In the present study, the number and nature of AEs was similar in both arms and consistent with the known safety profile of the study drugs. 7,28,29 However, five more drug reactions occurred in the combination arm, although this was statistically non-significant.…”
Section: Discussionsupporting
confidence: 66%
“…This is in agreement with one controlled trial that demonstrated the efficacy of trimethoprim/sulfamethoxazole plus rifampicin for MRSA decolonization. 27 In the present study, the number and nature of AEs was similar in both arms and consistent with the known safety profile of the study drugs. 7,28,29 However, five more drug reactions occurred in the combination arm, although this was statistically non-significant.…”
Section: Discussionsupporting
confidence: 66%
“…Clinical trials conducted in the 1990s demonstrated the efficacy of novobiocin-containing combinations for eradicating the carrier state of MRSA [19,20]. Indeed, novobiocin combined with rifampicin prevented the development of resistance in MRSA to either drug even more efficiently than the combination of co-trimoxazole and rifampicin [20].…”
Section: Discussionmentioning
confidence: 99%
“…Because novobiocin displays potent activity against staphylococci, including meticillin-resistant Staphylococcus aureus (MRSA), pneumococci, enterococci and many other Gram-positive organisms [5,6], during the 1980s the suitability of clinical reevaluation of this drug was suggested [6]. Clinical trials conducted in the 1990s demonstrated the efficacy of novobiocin-containing combinations for eradicating the carrier state of MRSA [19,20]. Indeed, novobiocin combined with rifampicin prevented the development of resistance in MRSA to either drug even more efficiently than the combination of co-trimoxazole and rifampicin [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family members who are living with MRSA carriers are exposed to MRSA transmission (Matsumoto et al, 2001). Antibiotics were shown to be effective with eradication rates only between 53% and 85% (Roccaforte et al, 1988;Walsh, et al, 1993;Asensio et al, 1996) But antibiotics are considered to be inappropriate for patients who are only colonized and not infected with MRSA and so in view of the high likelihood that the attempts to eradicate the MRSA carriership would fail in the long run, no treatment was prescribed.…”
Section: Discussionmentioning
confidence: 99%